Workload Analysis Using Cardiovascular Load and NASA-TLX Method Of Emergency Room Health Workers (Case Study: Rumah Sakit Tingkat III Brawijaya) - Melani Pratiwi Munir Putri; Akmal Suryadi (OPSI, 2022)
Emergency Room (ER) at RS Tingkat III Brawijaya is the first work unit that patients visit when they need first aid with various complaints. Kinds of patients in emergency medical services RS. Tingkat III Brawijaya are patients at risk of dying who require rapid treatment, patients not at risk of dying but requiring rapid treatment, and patients with non-critical and non-urgent conditions. The demands of time and professionalism from the emergency room health workers, that are the doctors and nurses when on duty, can have implications for the emergence of physical and mental burdens, including muscle pain, headaches and stress. This research purposed to analyze the physical and mental workload of emergency room health workers using the Cardiovascular Load and NASA TLX methods. The calculation results show that 5 health workers have a CVL percentage above 30, which is a repair that is needed but not urgent. Then with the NASA-TLX method, it is known that 21 health workers have a High workload and 2 others have a Very High workload category.